An accessory brachialis muscle associated with abnormal arrangement of structures in the cubital fossa - Akhtar, Md. Jawed; Fatima, Nafees; Kumar, Sanjay; Kumar, Binod; Kumar, Vinod (International Journal of Research in Medical Sciences, 2017)
An unusual variation of brachialis muscle was reported in the left superior extremity of a 61 year old North Indian female cadaver during routine dissection classes. It was observed that an additional belly of the accessory brachialis muscle was originated from the anteromedial surface of the shaft along with the medial supracondylar ridge of the left humerus. This additional muscle belly merged with the fibres of pronator teres in the cubital fossa & finally inserted on the lateral surface of the shaft of the radius, which was supplied by the musculocutaneous nerve. In the upper arm, the median nerve lies along the lateral side of brachial artery but at the middle of the arm the nerve did not cross from lateral to medial side rather it continue along the lateral side of the brachial artery. In the lower part, they passed superficial to the brachialis muscle but lie deep to this additional slip of muscle. After separating the fibres of muscles it was found that median nerve was present just lateral to the brachial artery in the cubital fossa, its contents from medial to lateral side were brachial artery, median nerve, accessory brachialis muscle, biceps tendon and radial nerve just under cover of brachioradialis. The knowledge about these variations is helpful to physicians while facing the patients of compression neuropathy of median nerve. Before planning the surgery around the elbow joint these variations should be considered to minimize the complications. These information are also useful to interventional cardiologist while performing brachial catheterization & radiologist also who performed various radio diagnostic procedures & angiographic studies around the cubital fossa.